PENINGKATAN SIKAP MANDIRI DAN HASIL BELAJAR MATERI PERKALIAN DAN PEMBAGIAN MENGGUNAKAN MEDIA STAMP GAME SISWA KELAS V SDN JONGKANG - Dian Rahasri, Brigitta; Purnomo, Puji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of independent attitude and learning outcomes of fifth grade students at SDN Jongkang in multiplication and division of whole numbers up to 100,000. This condition was identified from interviews with classroom teachers, learning observations, independent attitude questionnaires, and analysis of student learning outcomes. The learning process, which is still abstract and lacks concrete media, causes students to depend on teachers and friends. Therefore, this study aims to improve students' independence and learning outcomes through the use of the Stamp Game media. This study is a two-cycle classroom action research (CAR) with the research subjects being fifth-grade students at SDN Jongkang in the 2025/2026 academic year. Data collection techniques included observation, independent attitude questionnaires, learning outcome tests, and documentation, which were analyzed descriptively and quantitatively. The results of the study show that: 1) the use of the Stamp Game media was able to improve the independence and learning outcomes of fifth-grade students at SDN Jongkang in multiplication and division; 2) Students' independence increased from an average score of 43.97 at the beginning to 53.68 in cycle I and 69.31 in cycle II; 3) Students' learning outcomes improved, as indicated by the average score of 59.68 with a mastery level of 36% at the initial stage to 66.79 with a mastery level of 56% in cycle I and 74.79 with a mastery level of 84% in cycle II; 3) The effectiveness of using the Stamp Game media was reinforced by the results of the N-Gain Score analysis with a high category (0.7) for independent attitude and a moderate category (0.6) for learning outcomes.